My cyber self: identity presentation on TikTok - Karpova , Kateryna; Borymska , Oksana (Current issues of Ukrainian linguistics: theory and practice, 2022)
TikTok is a social network that has provided its users with a unique combination of communicative tools and, as a result, has laid the foundation for a new communication context for self-expression and identity presentation. The article examines how TikTokers’ discourse, with the help of the app’s technology, uses language means and other semiotic systems to present their self, to construct their online identities and to attract like-minded audiences. The study is based on 45 TikTok videos uploaded by different bloggers who were selected with the help of continuous sampling. The videos are analyzed by applying Critical Discourse Analysis and, in particular, Multimodal Discourse Analysis as frameworks for critical examination of verbal and nonverbal (images, soundtracks, clothes, etc.) means as well as contextual and intertextual structures of the TikTokers’ texts aimed at online self-expression and identify-presentation. The research reveals that the TikTokers avail themselves with syntactic patterns typical of self-presentation in order to assert their preferred selves and construct their identities by purposefully breaking away from conventional master identities, e.g., they claim either to be sex-neutral, or to be able to combine stereotypically incompatible identities, or to deny having any identity at all. To reflect on their selves and convey their message to the audience, the TikTokers use texts that feature intertextuality and multimodality. The merge of multimodal semiotic means helps the bloggers to create a complex of techno-semio-linguistic materiality typical of social media. The bloggers succeed in combining these diverse means so as to develop the intended meaning, to mediate their identities to their audience and, finally, to create their own communities rallied around the constructed identities.